Vertically resolved separation of dust and smoke over Cape Verde using multiwavelength Raman and polarization lidars during Saharan Mineral Dust Experiment 2008 - Tesche, Matthias; Ansmann, A.; Mueller, D.; Althausen, D.; Engelmann, R.; Freudenthaler, V.; Gross, S. (2009)
Multiwavelength aerosol Raman lidar in combination with polarization lidar at Praia (14.9 degrees N, 23.5 degrees W), Cape Verde, is used to separate the optical properties of desert dust and biomass burning particles as a function of height in the mixed dust and smoke plumes over the tropical North Atlantic west of the African continent. The advanced lidar method furthermore permits the derivation of the single-scattering albedo and microphysical properties of the African biomass burning smoke. A case study is presented to discuss the potential of the technique. The observations were performed during the Saharan Mineral Dust Experiment (SAMUM) in January and February 2008. The height-resolved lidar results are compared with column-integrated products obtained with Aerosol Robotic Network Sun photometer. Good agreement is found. Furthermore, the findings are compared with lidar and aircraft observations recently performed in western Africa and with our previous lidar observations taken in tropical and subtropical regions of southern and eastern Asia. The SAMUM case study represents typical aerosol layering conditions in the tropical outflow regime of western Africa during winter season. Above a dense desert dust layer (with an optical depth of about 0.25 at 532 nm) which reached to 1500 m, a lofted layer consisting of desert dust (0.08 optical depth) and biomass burning smoke (0.24 optical depth) extended from 1500 to 5000 m height. Extinction values were 20 +/- 10 Mm(-1) (desert dust) and 20-80 Mm(-1) (smoke) in the lofted plume. The smoke extinction-to-backscatter ratios were rather high, with values up to more than 100 sr, effective radii ranged from 0.15 to 0.35 mu m, and the smoke single-scattering albedo was partly below 0.7. Peer reviewed